"Don't know" answers concerning somatic disease status should not be regarded as "no" responses - Baumeister, Harald (GMS German Medical Science, 2008)
Background: With regard to patients' self-reported somatic diseases some researchers transformed “don't know (DK)” responses into “no” responses. The present study examines the appropriateness of this procedure. Methods: Analyses were based on the nationally representative German National Health Interview and Examination Survey (GHS), which assessed both self-reported diseases and physician-diagnosed diseases (N = 7124). Prevalence rates of persons’ DK responses and the corresponding prevalences of physicians’ diagnoses were calculated for persons with hypertension, coronary heart disease (CHD), heart failure, asthma, chronic bronchitis, thyroid disease, diabetes, cancer, gout, arthrosis, arthritis and osteoporosis. Correlates of physicians' diagnosed diseases of DK cases are reported. Results: Between 1.6% and 9.8% of the participants responded with DK to the question of whether they have the disease. In 3.7% to 29.5% of DK cases, the physicians did regard the respective disease as being present. With regard to persons who responded with DK, the probability of a physicians' diagnosis was increased in the case of increased age and a higher number of somatic comorbidities. Conclusion: The procedure of transforming DK responses into “no” answers does not appear to be recommendable.